L2 Vocabulary Knowledge and L2 Listening Comprehension: A Structural Equation Model - Li, Yang; Zhang, Xian (Canadian Journal of Applied Linguistics / Revue canadienne de linguistique appliquée, 2019)
The current study investigates how second language (L2) listening comprehension is associated with three dimensions of L2 vocabulary knowledge: size, depth, and fluency. Vocabulary knowledge tests administered to 290 participants measured L2 auditory vocabulary size, depth, and fluency. Afterward, participants took an International English Language Testing System (IELTS) listening test that measured L2 listening comprehension. Using a structural equation modeling technique, we found that all three dimensions of vocabulary knowledge are significant predictors of L2 listening comprehension. Size of auditory vocabulary in the L2 has the strongest predictive power over L2 listening comprehension. The results of the current study offer useful pedagogical implications for improving L2 listening comprehension.